Effect of a training program to improve the maximal oxygen uptake of soccer players of a team from the first division of the soccer of Costa Rica - Rivas-Borbón, Óscar Milton (2016)
Purpose: To determine the effect of an aerobic training program of aerobic power on Costa Rican professional soccer players. Subjects: 24 male subjects, with a mean age of 25.7 ± 3, 4 years. Instruments: The Yo-Yo test was used in the intermittent recovery version to assess possible changes in the aerobic power of the players. Procedure: for the preseason tournament for winter 2012 and summer 2013, a pre-test was applied to assess the current state their subsequently, they were put on a seven-week aerobic program. Finally, the post-test was applied to assess the effect of the training program. Statistical analysis: Descriptive statistics were applied as well as the non-parametric techniques of the Wilcoxon and Friedman test and t-student for repeated measures using the Statistical Package for Social Sciences SPSS (17 version), the significance level used was p ≤ 0.05. Results: A statistically significant improvement of the players’ maximum oxygen consumption was recorded. Conclusion: The proposed program improved the soccer players’ maximum oxygen consumption power of the players.